Evaluation of Serum Uric Acid in Type II Diabetes Mellitus Patients - P Pramod Kumar; Penta Goud (Asian Journal of Medical Research, 2015)
Introduction: To evaluate serum uric acid as a risk factor for diabetes mellitus. Subjects and Methods: 105 type II diabetes mellitus patients of both genders were selected in this study. 10 ml of venous blood was obtained in a test tube containing anticoagulant. Assessment of fasting and random blood glucose level, glycated hemoglobin (HbA1c) and uric acid level was done. Results: Age group 40-50 years comprised of 14 males and 10 females, 50-70 years had 16 males and 12 females and >70 years had 25 males and 23 female patients. The difference was non- significant (P> 0.05). Hyperuricemia was present in 65 and absent in 40. The difference was significant (P< 0.05). Conclusion: Most of the patients of type 2 diabetes mellitus had high serum uric acid level.